Is It Live? Liveness as Lure, or the (Live)Cast Illusion: The Director’s Cut - Siméon, Sandrine (Intermédialités / Intermediality, 2021)
Scholars and publics associate the term “liveness” with broadcasts of stage productions—but what does liveness refer to? This essay evaluates some of the protean forms the notion of liveness has so far assumed and proposes to underscore the motivated role of the broadcasts’ directors. Liveness emerges as an artifact of mediatization that encompasses more than an illusion of immediacy, a live-like feeling, or capitalizes on spectators’ habitus to lure them to screening venues. Liveness is in itself a performance that confirms the unique aesthetic of filmed theatrical productions designed to enhance and prioritize their viewers’ perspective.